2021
DOI: 10.3889/oamjms.2021.5869
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Intake, Zinc Serum Levels, and Intelligence in School Children in Rural Areas

Abstract: BACKGROUND: Children in rural areas are susceptible to zinc deficiency. Zinc deficiency in children can affect cognitive function in children. Zinc plays a role in cellular function and critical brain growth processes, including cell replication, DNA and RNA synthesis, and the release of neurotransmitters. AIM: This study aimed to analyze the condition of zinc deficiency and its relationship with the level of intelligence in children in rural areas. METHODS: The study design was cross-sectional, with a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…It showed that low zinc level increase the incidence of children have low intelligence 24.5 times compared to normal zinc and low socio-economic level causes insufficient intake of nutrients that rich of zinc such as nutrients from animal origin. In this study, the zinc results was fluctuating but showed low zinc level as risk factor, in accordance with research in developing country, weak socio-economic condition risky for insufficient intake of zinc-containing nutrients and risky for suffering chronic zinc deficiency that is not visible through serum zinc analysis [42].…”
Section: Discussionsupporting
confidence: 88%
“…It showed that low zinc level increase the incidence of children have low intelligence 24.5 times compared to normal zinc and low socio-economic level causes insufficient intake of nutrients that rich of zinc such as nutrients from animal origin. In this study, the zinc results was fluctuating but showed low zinc level as risk factor, in accordance with research in developing country, weak socio-economic condition risky for insufficient intake of zinc-containing nutrients and risky for suffering chronic zinc deficiency that is not visible through serum zinc analysis [42].…”
Section: Discussionsupporting
confidence: 88%
“…[7][8] Defisiensi terhadap seng pada periode remaja disebabkan oleh meningkatnya kebutuhan nutrisi untuk pertumbuhan yang cepat dan kebiasaan makan yang tidak tepat. 9 Riset Kesehatan Dasar di Indonesia yang dilakukan pada tahun 2013 menunjukkan bahwa insiden pada anemia perempuan usia sekolah dan remaja adalah 26,4% dan prevalensi anemia pada perempuan remaja dan dewasa adalah 18,4%. Sedangkan survey kesehatan nasional di Indonesia yang dilakukan pada tahun 2006 untuk mengetahui prevalensi anak kekurangan seng, berdasarkan data diperoleh prevalensi anak kekurangan seng adalah sebesar 36,1%.…”
unclassified